2020
DOI: 10.2147/dddt.s243787
|View full text |Cite
|
Sign up to set email alerts
|

<p>A First-in-Human Dose Finding Study of Camrelizumab in Patients with Advanced or Metastatic Cancer in Australia</p>

Abstract: Purpose: Camrelizumab inhibits PD-1 in non-clinical models and showed typical non-clinical pharmacokinetic (PK) and safety profiles for an IgG4 monoclonal antibody. We report results from the First-inHuman Phase 1 trial of camrelizumab in Australian population. Methods: Camrelizumab was administered to patients with advanced solid tumors who had failed standard therapies. In the dose-escalation phase (n=23), camrelizumab was administered intravenously at 1 mg/kg, 3 mg/kg, 6 mg/kg, and 10 mg/kg every 2 weeks. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 44 publications
(44 reference statements)
1
20
0
Order By: Relevance
“…After carefully screening the full text or conference abstracts, 24 articles were eligible. Finally, 15 articles with 1,390 patients were included after removing nine articles with duplicate data (Fang et al, 2018;Huang et al, 2019a;Huang et al, 2019b;Liu et al, 2019;Qin et al, 2019;Shen et al, 2019;Wu et al, 2019;Xie et al, 2019;Xu et al, 2019;Zhang et al, 2019;Zhou et al, 2019a;Zhou et al, 2019b;Chen et al, 2020a;Lickliter et al, 2020;Qin et al, 2020). Trial NCT03121716 had both a single-agent cohort (camrelizumab alone) and a combination cohort (camrelizumab plus other therapies), and the two cohorts were enrolled separately as two studies (Fang et al, 2018).…”
Section: Study Selectionmentioning
confidence: 99%
“…After carefully screening the full text or conference abstracts, 24 articles were eligible. Finally, 15 articles with 1,390 patients were included after removing nine articles with duplicate data (Fang et al, 2018;Huang et al, 2019a;Huang et al, 2019b;Liu et al, 2019;Qin et al, 2019;Shen et al, 2019;Wu et al, 2019;Xie et al, 2019;Xu et al, 2019;Zhang et al, 2019;Zhou et al, 2019a;Zhou et al, 2019b;Chen et al, 2020a;Lickliter et al, 2020;Qin et al, 2020). Trial NCT03121716 had both a single-agent cohort (camrelizumab alone) and a combination cohort (camrelizumab plus other therapies), and the two cohorts were enrolled separately as two studies (Fang et al, 2018).…”
Section: Study Selectionmentioning
confidence: 99%
“…The indications for camrelizumab are expanding through multiple ongoing clinical trials. A phase II clinical trial (NCT03912857) for treatment of patients with advanced mCRC, the combination of camrelizumab plus apatinib, a VEGFR2 inhibitor, is expected to increase the overall response rate of advanced mCRC after standard chemotherapy [183,184] (Table 1).…”
Section: Camrelizumabmentioning
confidence: 99%
“…Camrelizumab (SHR‐1210), a PD‐1 inhibitor, is being investigated as a treatment option for non‐squamous NSCLC 12 . A recent study (NCT02492789) showed that camrelizumab had encouraging antitumour activity in advanced solid tumours 13 . To the best of our knowledge, the evidence regarding the efficacy of camrelizumab for PSC is lacking.…”
Section: What Is Known and Objectivesmentioning
confidence: 99%